Anti-cancer effects of F16: A novel vascular endothelial growth factor receptor–specific inhibitor. Issue 11 (November 2017) - Rathinavelu, Appu; Alhazzani, Khalid; Dhandayuthapani, Sivanesan; Kanagasabai, Thanigaivelan
Vascular endothelial growth factor receptor-2 is a dynamic target for therapeutic intervention in various types of cancers. This study was aimed to explore the anti-angiogenic activity of a novel vascular endothelial growth factor receptor–specific inhibitor named F16 in both in vitro and in vivo experimental models. This compound effectively reduced cell proliferation, tube formation, and migration of human umbilical vein endothelial cells in a concentration-dependent manner by directly inhibiting vascular endothelial growth factor binding and subsequent vascular endothelial growth factor receptor-2 phosphorylation. The F16 was also able to inhibit the phosphoinositide 3-kinase/protein kinase B–mediated survival and migration pathways in cancer in addition to inhibiting the focal adhesion kinase and mitogen-activated protein kinases–mediated signaling in GI-101A cancer cells. The chorioallantoic membrane assay followed by tumor growth inhibition measurements with GI-101A breast cancer xenograft implanted athymic nude mice confirmed the in vivo tumor reductive effects of F16. It was interesting to observe a decrease in tumor burden after F16 treatment which correlated very well with the decrease in the plasma levels of mucin-1 (MUC-1). Our studies so far have confirmed that F16 is a specific inhibitor of angiogenesis in both in vitro and in vivo models. The F16 also works very efficiently with Taxol in combination by limiting the tumor growth that is better than the monotherapy with any one of the drugs that were tested individually. Thus, F16 offers a promising anti-proliferative and anti-angiogenic effects with better specificity than some of the existing multi-kinase inhibitors.